Prevalence and Degree of Infections Trichodina sp. Protozoa on Mujair (Oreochromis mossambicus) Resourses at Keramat Mengare Village, Bungah District, Gresik Regency. - Anita Munawwaroh; Lia Rahayu (BIOEDUKASI, 2017)
The disease of fish is the most common problems in fishery resources. Fish can get sickness due to several factors, including the existence of parasites, feed and environmental conditions that are less supportive of fish life. Tricodina sp. is an fish ectoparasite in freshwater and seawater, one of the freshwater fish that is often attacked is mujair (Oreochromis mossambicus). The purpose of research was to determine prevalence and degree of infections Tricodina sp. protozoa on mujair resourses. The research method is survey and random sampling. Location of sampling in ponds owned by farmers at Keramat Mengare Village, Bungah District, Gresik Regency. The result of research is prevalence and degree of infections Tricodina sp. is 91,87% and 54,81. Keywords: Prevalence, degree of infection, Trichodina sp., mujair (Oreochromis mossambicus).